Beyond 100 m Range Mini-LED-Based Visible Light Communication System - Zhijian Lv; Shuang Wu; Junye Zhong; Zikun Xu; Tiefeng He; Jinpeng Tian; Linfeng Zheng; Haichuan Zhang; Wenwei Zhang; Muxin Nian (Photonics)
In visible light communication (VLC) systems, lenses are typically used to collimate light at the transmitter. However, due to the wide light emission angle of mini-LEDs, capturing light at large angles using a lens at the transmitter can be challenging. This paper presents a design of a reflective cup at the mini-LED-based VLC transmitter. The redesigned reflective cup can collect most of the light and collimate it, achieving an efficiency of approximately 86% at a distance of 10 m in the simulation. In the experiment, error-free communication was achieved at a distance of 100 m with a data rate of 190 Mbps. To the best of our knowledge, a long-distance VLC system based on mini-LEDs is investigated for the first time. The reflective cup offers advantages, including high efficiency, low cost, and a simple structure. It holds reference value for addressing the issue of limited communication distance in underwater wireless optical communication (UWOC).